Analysis of students’ metacognition level in solving scientific literacy on the topic of static fluid - Zakaria Sandy Pamungkas; Nonoh Siti Aminah; Fahru Nurosyid (Journal of Education and Learning (EduLearn), 2019)
The purpose of this study is to describe students’ metacognition level in solving scientific literacy. This research use the descriptive method. The subject of this research is 99 students of grade XI in SMA Batik 2 Surakarta. Data collection methods used are test methods which its instruments based on an indicator of scientific literacy and metacognition ability. Data analysis techniques use quantitative descriptive analysis. The results showed that the achievement of scientific literacy in science as a body of knowledge, science as a way of thinking, science as a way of investigating, and science as an interaction between technology and society is still low at below 35%. This is due to 84%  student occupy in low metacognition level that is 30% students in tacit use level, 54% students in aware use level, and only 16% students occupy in high metacognition level that is in strategic use level.